Instructional Approaches in Facilitating English Learning for Students with Autism Spectrum Disorder - Al-Muniry, Faizah Thiwala Dahri; Ashadi, Ashadi (Edukasi, 2026)
This study investigates instructional approaches used in teaching English to students with Autism Spectrum Disorder (ASD) in an Indonesian special school context. Employing a qualitative case study design, the research involved two English teachers working in a special school (SLB). Data were collected through six classroom observations (two classes across three sessions) conducted between October and November 2025 over a one-month period through six classroom observation sessions conducted twice a week, as well as semi-structured interviews. The data were analyzed using thematic analysis. The findings reveal four key instructional approaches implemented by the teachers: direct instruction, differentiated instruction, multimodal teaching, and the application of Applied Behavior Analysis (ABA). These approaches were adapted to accommodate students’ diverse learning needs, attention spans, and communication abilities. In addition, the study identifies several challenges faced by teachers, including behavioral challenges, variation in student ability, limited learning resources, difficulty teaching English concepts, environmental constraints, lack of specialized training and support, students’ mood and sensory sensitivity. To address these challenges, teachers employed strategies such as individualized support., redirection techniques, the use of visual aids, the modification of teaching materials, collaboration with parents, as well as grouping and shifting. This study contributes to the existing literature by providing empirical insights into instructional practices for teaching English to students with ASD in the Indonesian special education context. The findings offer practical implications for educators in designing inclusive and effective language instruction for learners with ASD.